Natural light-micro aerobic condition for PSB wastewater treatment a flexible, simple, and effective resource recovery wastewater treatment process - Lu, Haifeng (Environmental technology, 2018)
Photosynthetic bacteria (PSB) have two sets of metabolic pathways. They can degrade pollutants through light metabolic under light-anaerobic or oxygen metabolic pathways under dark-aerobic conditions. Both metabolisms function under natural light-microaerobic condition, which demands less energy input. This work investigated the characteristics of PSB wastewater treatment process under that condition. Results showed that PSB had very strong adaptability to chemical oxygen demand (COD) concentration; with F/M of 5.2-248.5 mg-COD/mg-biomass, the biomass increased three times and COD removal reached above 91.5%. PSB had both advantages of oxygen metabolism in COD removal and light metabolism in resource recovery under natural light-microaerobic condition. For pollutants' degradation, COD, total organic carbon, nitrogen, and phosphorus removal reached 96.2%, 91.0%, 70.5%, and 92.7%, respectively. For resource recovery, 74.2% of C in wastewater was transformed into biomass. Especially, coexistence of light and oxygen promote N recovery ratio to 70.9%, higher than with the other two conditions. Further, 93.7% of N-removed was synthesized into biomass. Finally, CO2 emission reduced by 62.6% compared with the traditional process. PSB wastewater treatment under this condition is energy-saving, highly effective, and environment friendly, and can achieve pollution control and resource recovery